Impact of Digital Marketing on Online Purchase Intention: Mediation Effect of Customer Relationship Management - Dastane, Omkar (Journal of Asian Business Strategy, 2020)
This study investigated the impact of digital marketing on the online purchase intention of e-commerce consumers in Malaysia. In addition, the mediating effect of customer relationship management (CRM) between digital marketing and online purchase intention was also accessed because previous researchers have not detailed the mediating effect. A quantitative research method was applied to collect empirical data from 202 online shoppers selected by snowball sampling technique. Data were collected through a self-administered questionnaire in the greater Klang Valley region of Malaysia. Normality and reliability of the instrument were assessed using IBM SPSS 22, followed by confirmatory factor analysis and structural equation modelling using IBM SPSS AMOS 24. The validity of the measurement model and mediation analysis were carried out as per the research objectives. The results suggested that digital marketing had a positive significant impact on online purchase intention. However, the mediating effect of CRM was found to be insignificant. The study contributed to the literature by providing a structural model of digital marketing and purchase intention to measure the impact of digital marketing on online purchase intention in the context of Malaysian e-commerce. The paper then discussed the implications, limitations, and future research opportunities.